Семантична типологія афоризмів (на матеріалі сучасного художнього дискурсу) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The thesis deals with the complex investigation of the semantic typology of aphorisms. The language status and specific character of aphorisms in modern Ukrainian are substantiated; the ties between their semantic, cognitive structure are investigated. A Ukrainian aphorism study is analyzed in close connection with its semantic peculiarities, with enlisting materials from ethnolingvistics, ethnocultural studies and psychology.